Pengukuran dan Evaluasi Keamanan Informasi Menggunakan Indeks KAMI - SNI ISO/IEC 27001:2009 - Irawan Afrianto; Taryana Suryana; Sufa’atin Sufa’atin (ULTIMA InfoSys, 2015)
Information is a valuable asset for the college. The need for safeguards against information becomes very necessary thing for a college. One standard that can be used to measure the maturity level of information security in an organization is the KAMI index developed by Depkominfo standards refer to ISO standard ISO / IEC 27001: 2009. This assessment is used to see how far the maturity level of information security in the college environment, which results can be used as a medium for evaluation in order to improve the information security of the college in the future. Index Terms - Assessment, Information security, KAMI Index, Maturity Level, College X